Effectiveness of T cell–mediated rejection therapy: A systematic review and meta‐analysis. Issue 3 (10th December 2021) - Ho, Julie; Okoli, George N.; Rabbani, Rasheda; Lam, Otto L. T.; Reddy, Viraj K.; Askin, Nicole; Rampersad, Christie; Trachtenberg, Aaron; Wiebe, Chris; Nickerson, Peter; Abou‐Setta, Ahmed M.
Abstract : The effectiveness of T cell–mediated rejection (TCMR) therapy for achieving histological remission remains undefined in patients on modern immunosuppression. We systematically identified, critically appraised, and summarized the incidence and histological outcomes after TCMR treatment in patients on tacrolimus (Tac) and mycophenolic acid (MPA). English‐language publications were searched in MEDLINE (Ovid), Embase (Ovid), Cochrane Central (Ovid), CINAHL (EBSCO), and Clinicaltrials.gov (NLM) up to January 2021. Study quality was assessed with the National Institutes of Health Study Quality Tool. We pooled results using an inverse variance, random‐effects model and report the binomial proportions with associated 95% confidence intervals (95% CI). Statistical heterogeneity was explored using the I 2 statistic. From 2875 screened citations, we included 12 studies (1255 participants). Fifty‐eight percent were good/high quality while the rest were moderate quality. Thirty‐nine percent of patients (95% CI 0.26–0.53, I 2 77%) had persistent ≥Banff Borderline TCMR 2–9 months after anti‐rejection therapy. Pulse steroids and augmented maintenance immunosuppression were mainstays of therapy, but considerable practice heterogeneity was present. A high proportion of biopsy‐proven rejection exists after treatment emphasizing the importance of histology to characterize remission. Anti‐rejection therapy is foundational to transplant management but well‐designed clinical trials in patients on Tac/MPA immunosuppression are lacking to define the optimal therapeutic approach. Abstract : A systematic review and meta‐analysis found a high prevalence of persistent T cell‐mediated rejection after anti‐rejection therapy, highlighting the need for more effective therapies. Chandran comments on page 683 .